The Impact of Digital Da'wah Media on Religious Literacy among Eleventh-Grade Female Students at MAN Insan Cendekia OKI - Saidina Saidina; Aina Warda Agissa; Yuniar Yuniar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the effect of using digital da'wah media in improving religious literacy in grade XI students of MAN Insan Cendekia OKI. In the midst of a fast and massive flow of information, digital da'wah comes as a fresh and relevant approach for Generation Z. This study uses a quantitative approach with a simple linear regression method on 30 randomly selected respondents. The results showed that digital da'wah has a significant and positive influence on religious literacy. It is known that 70.5% of variations in the level of religious literacy can be explained by the intensity of access to digital da'wah. This proves that digital media is not only a means of entertainment, but can also be an effective educational medium to shape moderate and critical religious understanding among adolescents. This research is expected to be an inspiration for preachers, educational institutions, and the younger generation in utilizing technology to strengthen religious values in a positive way.